Crystallographic and magnetic properties of REInAu2 intermetallics - Besnus, M.J.; Kappler, J.P.; Meyer, A.; Sereni, J.; Siaud, E.; Lahiouel, R.; Pierre, J.; Sereni, Julián (Elsevier, 1985)
Fil: Sereni, J. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina